Conglomerate Diversification Strategy: good or bad? – Evidence from Vietnam - Trang, Nguyen Thi Xuan (Marketing & Menedzsment, 2018)
THE AIMS OF THE PAPER The paper aims to check the effectiveness of conglomerate diversification strategy in case of Vietnam by testing the relationship between unrelated diversification level and firm value of listed companies in this country. METHODOLOGY A sample of 70 listed firms in Vietnam during the period from 2007 to 2014 is collected in the research. With the feature of a balanced panel data set, three regression methods consisting of Pooled OLS regression, Fixed effects model and Random effects model, are, in turn, applied thanks to Stata 12.0. After that, F test and Hausman test are used to find out the most preferable method to the model. Problems of multicollinearity, heteroscedasticity, autocorrelation and endogeneity are also considered in testing. MOST IMPORTANT RESULTS There are no statistical evidences to assert the negative relationship between conglomerate diversification level and firm value through Tobin’s q at 5% significant level. It can be explained that from 2007 to 2014, the average diversification level for each listed firm in Vietnam was quite low, less than 0.2. Thus, diversifying into new industries that were rather different from the core industries could bring not only challenges but also opportunities for the firms in this country in the current era of globalization. RECOMMENDATIONS It is recommended that implementing conglomerate diversification strategy of a company should be revised when unrelated diversification level reaches to a certain maximum amount that is expected to make this strategy go counter to benefits of the principals.